A fast in situ hybridization chain reaction method in Drosophila embryos and ovaries - Kyohei Mikami; Yasuhiro Kozono; Masaki Masukawa; Satoru Kobayashi (Fly)
The in situ hybridization chain reaction (isHCR) is a powerful method for visualizing mRNA in many species. We present a rapid isHCR method for Drosophila embryos and ovaries. Ethylene carbonate was added to the hybridization buffer to facilitate the hybridization reaction, and a modified short hairpin DNA was used in the amplification reaction; these modifications decreased the RNA staining time from 3 days to 1 day. This method is compatible with immunohistochemistry and can detect multiple mRNAs. The proposed method could significantly reduce staining time for Drosophila researchers using isHCR.